1989
DOI: 10.1164/ajrccm/140.6.1650
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistopathologic Localization ofPseudomonas aeruginosain Lungs from Patients with Cystic Fibrosis: Implications for the Pathogenesis of Progressive Lung Deterioration

Abstract: Despite studies of the pathologic and microbiologic aspects of the lung in cystic fibrosis (CF), there is a lack of information on the lung localization of bacterial pathogens. Bacteriologic data come from cultures of sputum or accessible lung effluent from bronchoscopy. Our objective was to localize Pseudomonas aeruginosa (PA) in situ in order to provide descriptive data on the relationship between the presence of PA and disease of the surrounding tissue. Using stored, uncut blocks of preserved lung, we depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
156
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(177 citation statements)
references
References 3 publications
12
156
1
Order By: Relevance
“…Therefore, relying on observations made from the pathologic and histopathologic analysis of affected tissues provides substantial insight into the pathogenesis of this disease. Observations of the CF airway epithelium in tissues taken at autopsy or transplant [5][6][7] and observations made during experimental infection of WT and transgenic CF mice [8] clearly show that P. aeruginosa rarely binds to the airway epithelial cells in the CF lung but does so vigorously in mice expressing WT-CFTR (Figure 1a-d).…”
Section: Pseudomonas Aeruginosa In Cystic Fibrosismentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, relying on observations made from the pathologic and histopathologic analysis of affected tissues provides substantial insight into the pathogenesis of this disease. Observations of the CF airway epithelium in tissues taken at autopsy or transplant [5][6][7] and observations made during experimental infection of WT and transgenic CF mice [8] clearly show that P. aeruginosa rarely binds to the airway epithelial cells in the CF lung but does so vigorously in mice expressing WT-CFTR (Figure 1a-d).…”
Section: Pseudomonas Aeruginosa In Cystic Fibrosismentioning
confidence: 99%
“…One recent study suggested this switch make take as long as 10 years, on average, before mucoid P. aeruginosa is routinely detected by microbiologic cultures [1]. Although many studies, conducted almost exclusively in υitro using cultured cells, have proposed that other P. aeruginosa surface factors such as pili, lectins and other adhesins can influence epithelial cells and initiate such responses as activation of the NF-κB innate immune response pathway associated with subsequent proinflammatory gene expression [40], this does not appear too relevant to CF as P. aeruginosa is never observed to bind to the CF epithelium in υiυo [5][6][7]. Furthermore, this organism only minimally binds to the respiratory epithelium of transgenic CF mice within hours of experimental infection [8].…”
Section: P Aeruginosa Virulence Factors Impacting the Cf Lung Responmentioning
confidence: 99%
See 2 more Smart Citations
“…Normal respiratory epithelium forms a protective barrier against colonization by bacteria. Its loss in airways of CF patients has been associated with the presence of Pseudomonas aeruginosa [26]. Airway epithelial injury and repair favour bacterial adherence and may thus contribute to the airway infection in CF [27].…”
Section: Airway Dimensionsmentioning
confidence: 99%